Distinct RopGEFs successively drive polarization and outgrowth of root hairs - Denninger, Philipp; Denzler, Anna; Schmidt, Vanessa Aphaia Fiona; Keinath, Nana; Evers, Jan-Felix; Großmann, Guido (Current biology, 2019)
Root hairs are tubular protrusions of the root epidermis that significantly enlarge the exploitable soil volume in the rhizosphere. Trichoblasts, the cell type responsible for root hair formation, switch from cell elongation to tip growth through polarization of the growth machinery to a predefined root hair initiation domain (RHID) at the plasma membrane. The emergence of this polar domain resembles the establishment of cell polarity in other eukaryotic systems [1, 2, 3]. Rho-type GTPases of plants (ROPs) are among the first molecular determinants of the RHID [4, 5], and later play a central role in polar growth [6]. Numerous studies have elucidated mechanisms that position the RHID in the cell [7, 8, 9] or regulate ROP activity [10, 11, 12, 13, 14, 15, 16, 17, 18]. The molecular players that target ROPs to the RHID and initiate outgrowth, however, have not been identified. We dissected the timing of the growth machinery assembly in polarizing hair cells and found that positioning of molecular players and outgrowth are temporally separate processes that are each controlled by specific ROP guanine nucleotide exchange factors (GEFs). A functional analysis of trichoblast-specific GEFs revealed GEF3 to be required for normal ROP polarization and thus efficient root hair emergence, whereas GEF4 predominantly regulates subsequent tip growth. Ectopic expression of GEF3 induced the formation of spatially confined, ROP-recruiting domains in other cell types, demonstrating the role of GEF3 to serve as a membrane landmark during cell polarization.
Gesehen am 28.01.2020